DETERMINING MAQASHID AL SHARIA BASED COMPLIANCE FOR REAL SECTOR BUSINESS APPROACH AND METHODOLOGY - Ika Yunia Fauzia; Maisyarah Stapah Salleh; Nizam bin Ahmat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Since the studies on sharia compliance are dominated by the financial sector and the absence of a standard on how shari'ah compliance in the real business sector, this study then aims to formulates a framework on how to linked between sharia compliance as measured by maqashid al-sharia and real business sector by using content analysis and case study methodology. The theoretical foundation in this study is the discussion of how Muslim businessmen behave in Indonesia in running their business and how to operate sharia Maqashid in the business sector. The results of this study indicate that sharia compliance in real sector business has own meaning, form, role, values, and also principles in its implementation